Kajian analisis biaya dan manfaat (cost-benefit analysis) kawasan agrowisata di Indonesia - I Gusti Bagus Ananta Wijaya Putra; Agung Prijanto; Ni Made Classia Sukendar; Gede Mekse Korri Arisena (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Agrotourism is a part of the tourist attraction that utilizes agricultural business as a tourist attraction. This study aims to compare financial feasibility studies on several agrotourism in Indonesia. The study about financial feasibility needs to be done as a material consideration in making a business decision. The method used a literature study for secondary data collection from several journals including NPV, IRR and Net B/C Ratio. This study reviews five agrotourism, that relates with cost-benefit analysis, including Kebun Buah Mangunan agrotourism, Kampung Budaya Sidangbarang agrotourism, Bukit Ganjau agrotourism, Bina Darma agrotourism, and Jamu Ramuan Madura agrotourism. The results of this study were obtained at Jamu Ramuan Madura agrotourism that was the most feasible with an NPV value of Rp. 13,979,701,973.49, - IRR of 30.52%, and Net B/C Ratio of 10.22 which indicated this agrotourism was feasible to run. This agrotourism is the most feasible because it has the highest value among the five other agrotourism. Kampung Budaya Sidangbarang agrotourism is the lowest feasibility level because it has an NPV value of Rp. 597,264,637.59, - with a Net B/C value of 1.60 and an IRR of 15.13%. Based on this, it is expected that the results of this study can become a reference for tourism developers to see the potential of agrotourism in areas that have the best financial viability.